A Consumer Perspective of the Impact of Corporate Social Responsibility (CSR) Efforts and Negative Externalities on Brand Image - Wahyudi, Diana Rikasari (2007)
Nowadays, companies are increasing their participation towards the implementation of Corporate Social Responsibility (CSR) to help build, and in some cases, repair their brand images. Companies market their CSR initiatives to the public in general and consumers in particular, in hopes that such efforts will result in a higher degree of positive reception from the public and consumers. On the other hand, there exist external parties which equally attempt to expose negative information about companies. While a company vigorously promotes their socially responsible acts to the consumers through various means including advertisements, consumers are also exposed to negative facts and stories about the company. Therefore, consumers are left with varied information containing opposing views about a company. In these circumstances, this study is my modest contribution to the intriguing phenomenon. It asks a series of questions about how consumers’ perceive this situation, especially, what, if any, significance does a company’s CSR initiatives and the negative information being present have upon the company’s brand image. In fashioning the answer to this obscurity, one might simply assume that the degree of their impact is great. This may seem to be a plausible assumption in this context, since information that consumers receive typically become a consideration of how they evaluate products and its brands. In attempting, a quantitative-based research is employed using McDonald’s Corporation as a study case. Multiple regression analyses were performed to uncover the relationship between CSR initiatives and negative externalities with McDonald’s brand image, whereas findings implied an original discovery. Results indicate that such information appear to have a low influence towards how consumers’ perceive the company’s brand image. Based on the findings, this research provides implications to businesses in Malaysia, a developing country, whose consumers may have different meanings of CSR and negative information compared to consumers of the developed countries- specially the Western countries.